Testicular seminoma: Clinical presentation and management of local recurrence - Chowksey, Sanjeev R; Sawarkar, Shriniket (Indian Journal of Case Reports, 2020)
Over 95% of testicular cancers are curative, with surgery alone. Local recurrence of testicular cancer though reported less but frequently involves the scrotal and inguinal regions, including superficial inguinal lymph nodes. We describe a case of local recurrence of testicular cancer in a non-violated scrotum, a finding that has not been previously reported in the literature. A 37-year-old male laborer presented with swellings in the right side scrotum and the right side inguinal region for 1 month. Histopathology was suggestive of seminoma right testis, after which the patient was given bleomycin, etoposide, and cisplatin chemotherapy, which included six cycles with an interval of 2 weeks followed by 20 cycles of radiotherapy cobalt 60, i.e., 20 cycles for 1 year. After chemotherapy, the patient reported by presenting symptoms in our hospital. For further evaluation of swellings in scrotum and groin, a series of investigations were carried out, which included blood and radiological investigations to confirm the diagnosis which was suggestive of local recurrence at the incision site as well as in the scrotum. The oncologist opinion suggested to administer regime (vinblastine, ifosfamide, and cisplatin) for four cycles and was assessed with follow-up.